2012
DOI: 10.1186/gb-2012-13-5-158
|View full text |Cite
|
Sign up to set email alerts
|

Power to the people: a wiki-governance model for biobanks

Abstract: Biobanks are adopting various modes of public engagement to close the agency gap between participants and biobank builders. We propose a wiki-governance model for biobanks that harnesses Web 2.0, and which gives citizens the ability to collaborate in biobank governance and policymaking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 56 publications
3
28
0
1
Order By: Relevance
“…The importance of obtaining such input is rooted in the pivotal role of public's contribution to genomics research, accentuating the need to accommodate their views and concerns in future policy makings [32][33][34][35], leading to responsive and progressive genomics research practices. In particular, the potential problems associated with sharing the results of genomic studies through public databases in an open or controlled fashion, as discussed above, require a clear understanding of public opinion.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of obtaining such input is rooted in the pivotal role of public's contribution to genomics research, accentuating the need to accommodate their views and concerns in future policy makings [32][33][34][35], leading to responsive and progressive genomics research practices. In particular, the potential problems associated with sharing the results of genomic studies through public databases in an open or controlled fashion, as discussed above, require a clear understanding of public opinion.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we shifted focus to another mass medium – Facebook – to maintain focus on retrospective biobank participants, taking advantage of a dynamic platform that would enable viewers’ questions, interests and concerns to be readily communicated and answered. Public health social marketing campaigns enable an important feature of community engagement: the ability to receive feedback from targeted communities in real time [26, 29, 51]. In addition to effecting community engagement for its own sake, our outreach, including the social media campaign, has shed light on the sur-mountability of the obstacles on the path to an informed public.…”
Section: Discussionmentioning
confidence: 99%
“…Social media has long been identified as relevant to biobanking, particularly in its capacity to expand the reach and effectiveness of community engagement [2729]. A study of potential participation in cancer biobanks found that social media could be a powerful tool for communicating with 18–29-year-olds in particular [30].…”
Section: Introductionmentioning
confidence: 99%
“…Par exemple, un projet de recherche en génomique sur une maladie orpheline pourrait faire appel à l'externalisation ouverte pour recruter des patients atteints de cette maladie, pour trouver des commanditaires prêts à financer la recherche ou pour déléguer certains aspects de celle-ci à des collaborateurs externes. L'externalisation ouverte est un modèle participatif où les personnes intéressées à contribuer au projet peuvent aussi se voir octroyer la possibilité d'influer, à différents niveaux, sur la direction future de la recherche [23]. Les avantages d'utiliser l'externalisation ouverte dans le domaine de la médecine personnalisée sont nombreux : recruter plus de participants et mieux connaître leurs attentes, réduire les coûts de production des tests et médicaments en distribuant de façon stratégique les différentes activités de recherche et de dévelop-pement à des collaborateurs externes, avoir accès à un plus grand vivier d'investisseurs intéressés au projet, etc.…”
Section: La Médecine Personnalisée : Un Vecteur De Changement Positifunclassified